Fatphobia and the polemic “romanticization of obesity” through the eyes of Brazilian high school students - Nerim, Maria Isabel; Miranda, Mayker Lazaro Dantas (Educere et Educare, 2023)
ABSTRACT: Prejudice against fat people, the so-called fatphobia, keeps affecting many people in schools. Body standardization has always been socially internalized but it is sad to know that cases of fatphobia keep taking place in schools and outside them. The fat are stereotyped as unable and are rarely chosen by their classmates to take part in collective activities. Besides, they are often embarrassed and offended. On the other hand, it is now more common to see people advocating obesity as a movement which makes people accept their own bodies in an attempt to end prejudice. As a current theme, the polemic romanticization of obesity is a risk when only the aesthetic appeal is considered. Above all, obesity is a disease that is associated with several comorbidities, such as diabetes, hepatic steatosis and arterial hypertension. Therefore, this study aimed at investigating how this issue is understood by High School students who attend the Instituto Federal do Triângulo Mineiro - Campus Uberlândia Centro, in Uberlândia, MG, Brazil, and how it affects their everyday lives. This basic, fundamental, qualitative and exploratory study collected data on “fatphobia versus romanticization of obesity” in High School. Highly connected students gave their opinions and showed how important and updated it is to address this topic in school since the social media and several people disagree regarding the dichotomy between “treating yourself” and “accepting yourself”.